2013
DOI: 10.5539/ijbm.v8n10p1
|View full text |Cite
|
Sign up to set email alerts
|

Directors’ Connections, Financial Resources and Performance: An In-Depth Analysis of Canadian Companies

Abstract: Despite numerous studies, there is still no consensus about the impact of the board on firm performance. Previous research has focused mainly on the economic and financial aspects of the director's role, but scant attention has been paid to its relational aspect. Some authors have suggested that directors' social networks (connections) could be used to help the firm acquire external resources. This paper delves into the impact of three types of director connections on the firm's resources and financial perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 68 publications
1
14
0
Order By: Relevance
“…ROA, ROE and solvency were negatively influenced by political connections. These results partially confirmed our hypothesis and partially supported previous findings related to companies in other industries, which have shown that political connections have a positive effect on financial performance (Dicko & Breton, 2013a;Dicko & El Ibrami, 2013;Dicko & Khemakhem, 2015). …”
Section: Conclusion and Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…ROA, ROE and solvency were negatively influenced by political connections. These results partially confirmed our hypothesis and partially supported previous findings related to companies in other industries, which have shown that political connections have a positive effect on financial performance (Dicko & Breton, 2013a;Dicko & El Ibrami, 2013;Dicko & Khemakhem, 2015). …”
Section: Conclusion and Discussionsupporting
confidence: 82%
“…Research has demonstrated that companies with political connections perform better financially and have easier access to finances, in both the Canadian context (Dicko & Breton, 2013a;2013b;Dicko & El Ibrami, 2013;Dicko & Khemakhem, 2015;Khemakhem & Dicko, 2013) and around the world (Hillman, Zardkoohi, & Bierman, 1999;Goldman, Rocholl, & So, 2009;Fisman, 2001;Hillman, 2005;Goldman, Rocholl, & So, 2013;Li & Xia, 2013;Houston, Jiang, & Yuema, 2014;Yan, Wu, & Wilson, 2014). Until now, almost no studies have been conducted on financial institutions.…”
Section: Introductionmentioning
confidence: 99%
“…Most prior literature focused on the impact of firms' political connections on their financial performance and access to resources, such as loans and contracts. This research was carried out not only in the U.S. (Goldman et al, 2009), but also in Canada (Dicko and El Ibrami, 2013;Dicko and Khemakhem, 2015) as well as elsewhere in the world (Claessens et al, 2008 In the Canadian context, Dicko (2016) demonstrated that politically connected Canadian firms listed on the S&P/TSX composite index are awarded more numerous and lucrative federal government contracts than non-politically connected firms are. Similar results were obtained by Goldman et al (2013) and Wang (2014) in the U.S. Dicko and Khemakhem (2015) also show that the political connections of S&P/TSX Canadian firms are positively and significantly related to their return on assets.…”
Section: Financial Impact Of Corporate Political Activitiesmentioning
confidence: 99%
“…Most previous studies of politically connected companies have looked at financial performance and have shown that politically connected corporations perform better than firms without political links (Ang et al, 2013;Dicko and Breton 2013a;2013b;and El Dicko Ibrami, 2013;Li and Xia, 2013). These studies, conducted mainly in the United States and Canada, have shown that companies with connections have better market (Goldman et al, 2009) and accounting performances (Dicko and Khemakhem, 2015) than companies that are not connected.…”
Section: The Impact Of Political Connections On Firmsmentioning
confidence: 99%
“…In the literature, a company is considered politically connected if its majority shareholder or one of its executive officers or board members is or has been a member of government, prime minister or head of government, member of parliament, member or leader of a political party, has a connection to politicians and/or has contributed or currently contributed to political parties (Faccio, 2006;Dicko, 2011;Dicko and Breton, 2013a;2013b;El Dicko Ibrami, 2013).…”
Section: A-political Connectionsmentioning
confidence: 99%